Equality of Education Quality in Indonesia through Education Reform - Deding Ishak (IHSA Institute, 2022)
The era of globalization causes the need for changes in various fields, including education. One of the steps that can be used to improve the quality of education is through equal distribution of education. Therefore, this research will look at how the implementation of education in Indonesia through the zoning system and its comparison with countries that have implemented this before. The research will be carried out using a qualitative approach with data sources and previous studies. The results of this study indicate that there are many challenges for the Indonesian state to follow this system. But slowly, the Indonesian state can overcome this problem by providing the same facilities as the system abroad.